Immunological and central nervous system changes in mice suffering from Staphyloccocus aureus and treated with Saccharomyces cerevisiae var. vini living cells - Ochigava, I; Kalandarishvili, L; Zhvania, M (Folia microbiologica, 2006)
The influence of Saccharomyces cerevisiae var. vini viable cells on the Staphylococcus aureus-suffering mice was ascertained: (1) effect of S. aureus living cells on antibacterial and antitoxic antibodies, (2) effect of S. aureus on the number of neurons and macroglial cells in different areas of mouse hippocampus, (3) effect of S. cerevisiae var. vini viable cells on the above-mentioned changes of immune and nervous system. Treatment with S. cerevisiae var. vini provokes immune stimulation and change of the total number of macroglial elements in the CA1 field of hippocampus.
Keywords: histocytochemie; modely nemocí na zvířatech; stafylokokové infekce; Histocytochemistry; Male; Staphylococcus aureus; Brain; probiotika; Saccharomyces cerevisiae; mužské pohlaví; neurony; hipokampus; Hippocampus; mikroglie; Animals; zvířata; Microglia; Neurons; Disease Models, Animal; Staphylococcal Infections; mozek; protilátky bakteriální; myši; Probiotics; Mice; Antibodies, Bacterial